1970
DOI: 10.5424/sjar/2012101-021-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and heritability in cultivated okra [Abelmoschus esculentus (L.) Moench]

Abstract: Twenty-nine okra accessions from different agro-ecological regions in Nigeria were grown during the rainy and dry seasons, between 2006 and 2007 at Abeokuta (derived savanah) and Ilishan (rainforest) and assessed to determine their genetic variability, heritability and genetic advance from eight yield related characters. The experiment was laid out in a Randomized Complete Block Design with five replications. There was high genotypic coefficient of variability, % broad-sense heritability and genetic advance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 8 publications
23
19
0
Order By: Relevance
“…It shows that the genetic parameters of the parental materials were quite dissimilar. This result corroborates with that of several earlier researchers (Akinyele & Osekita, 2006;Nwangburuka et al, 2011;Nwangburuka et al, 2012;AdeOluwa & Kehinde, 2013;Muluken et al, 2016). Again, the cultivars exhibited significant (P<0.05) differences for fresh capsule yield per plant and the number of capsules per plant.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It shows that the genetic parameters of the parental materials were quite dissimilar. This result corroborates with that of several earlier researchers (Akinyele & Osekita, 2006;Nwangburuka et al, 2011;Nwangburuka et al, 2012;AdeOluwa & Kehinde, 2013;Muluken et al, 2016). Again, the cultivars exhibited significant (P<0.05) differences for fresh capsule yield per plant and the number of capsules per plant.…”
Section: Resultssupporting
confidence: 92%
“…This variation could be used via selection to improve the okra studied characters. This result is supported by several previous researchers (Düzyaman, 2005;Salesh et al, 2010;Nwangburuka et al, 2012;Hazem et al, 2013;Amoatey et al, 2015). The first-order cultivar × year interaction was significant for all the okra characters.…”
Section: Resultssupporting
confidence: 86%
“…Hence, phenotypic selection may not hold good for genetic improvement in these traits. These findings are in agreement with Dastidar et al, (1993), Islam et al, (2002), Palve et al, (2003), Echekwu and Showemino (2004), Ibrahim and Hussein (2006), Ghodke and Wadikar (2011);Nwangburuka et al, (2012) and Ibrahim et al, (2013 Similar results were also reported by Dastidar et al, (1993), Mostofa et al, (2002), Echekwu and Showemino (2004), Ghodke and Wadikar (2011);Nwangburuka et al, (2012) and Ibrahim et al, (2013 High heritability coupled with high genetic advance of mean was observed for the traits plant height, pods plant -1 and seed yield plant -1 in both the years. These findings were corroborated with the results of Dastidar et al, (1993), Islam et al, (2002), Ghodke and Wadikar (2011);Nwangburuka et al, (2012) and Ibrahim et al, (2013).…”
Section: Resultssupporting
confidence: 90%
“…These findings are in agreement with Dastidar et al, (1993), Islam et al, (2002), Palve et al, (2003), Echekwu and Showemino (2004), Ibrahim and Hussein (2006), Ghodke and Wadikar (2011);Nwangburuka et al, (2012) and Ibrahim et al, (2013 Similar results were also reported by Dastidar et al, (1993), Mostofa et al, (2002), Echekwu and Showemino (2004), Ghodke and Wadikar (2011);Nwangburuka et al, (2012) and Ibrahim et al, (2013 High heritability coupled with high genetic advance of mean was observed for the traits plant height, pods plant -1 and seed yield plant -1 in both the years. These findings were corroborated with the results of Dastidar et al, (1993), Islam et al, (2002), Ghodke and Wadikar (2011);Nwangburuka et al, (2012) and Ibrahim et al, (2013). High heritability coupled with high genetic advance as percent of mean for plant height, pods plant -1 and seed yield plant -1 indicates the operation of additive genes and offer the best possibility for improvement of this trait through mass selection, progeny selection, family selection to any other suitable modified selection procedure aiming to exploit the additive gene effects Bhakuni (Bhakuni Vandana) (Vandana et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…This is in accordance with the reports of Nwangburuka et al (2012) and Olawuyi et al (2014) who considered genetic variability as essential in crop breeding. The genotypic effect also had significant expression on the traits evaluated in Amaranthus.…”
Section: Discussionsupporting
confidence: 93%